HUBUNGAN TINGKAT PENGETAHUAN TENTANG NARKOBA DAN STIGMA PADA PECANDU NARKOBA DENGAN MOTIVASI TIDAK MEMAKAI NARKOBA PADA REMAJA - Endang Dwi Ningsih; Emanuela Veren Gravita Kusuma (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2018)
Background: The circulation of drugs in Indonesia has penetrated in all of the society levels, this condition is very worrying for the sustainability of the nation. The prevalence of drug abuse in group of students and college students in 2016 is 3.8%, where every year experiencing significant fluctuations. Related to the above, it is necessary to research about the relationship between the level of knowledge about drugs and the stigma of drug addicts with the motivation not to use drugs in teenagers GBI Emunah Solo Baru Sukoharjo. Objective: To know the correlation between the level of knowledge about drugs and stigma on drug addicts with the motivation not to use drugs in adolescents. Research Subject: Research sample are 63 teenagers / youth of GBI Emunah Solo Baru Sukoharjo by using Saturation sampling technique. Research Subject: Research sample are 63 teenagers / youth of GBI Emunah Solo Baru Sukoharjo by using Saturation sampling technique. Result of the research: By Bivariate test obtained the result p = 0.000 and p <0.05. By Multivariate test obtained result of value Negelkerke Square 60.3% Conclusion: There is a relationship between the level of knowledge about drugs with the motivation of not using drugs, and there is also a relationship between the stigma of drug addicts with the motivation not to use drugs. That the level of knowledge about drugs and stigma in drug addicts together related to non-drug motivation 60.3% while the remaining 39.7% influenced by other variables outside the study. Keywords: Motivation not to use drugs, stigma in drug addicts and level of knowledge about drugs